(untitled) (Training and Practice : Journal of Educational Sciences, 2010)
In the 21. century the individual’s competence development the focus of vocational training due to the lifelong learning paradigm. Its basic aim is to develop action skills and cooperative skills. The results of the reform of vocational training system are the more and more cooperative and beneficial vocational qualifications, the guarantee of transit among them, the credit compensation of the previous qualifications, and the creation of a trade market that fits the labour market demands. Module system makes more efficient training possible with branches and postgraduate vocational trainings. Those who choose one of business management vocational higher education programmes can get a marketable trade in two years, or can continue their studies on BA level with the compensation of their credits.